Evaluating Bali’s Financial Performance: Pre, During, and Post-Covid-19 - Pangestu, Alya Diajeng; Saraswati, Erwin (E-Jurnal Akuntansi, 2026)
This study analyzes the financial performance of the Bali Provincial Government before, during, and after the Covid-19 pandemic. The pandemic significantly impacted Bali's economy, heavily dependent on tourism and Local Own-Source Revenue (PAD). This research employs a quantitative descriptive method using audited data from Bali’s Budget Realization Report (2018–2023). Results show a sharp decline in PAD and financial independence during 2020–2021, followed by a recovery in 2022–2023, particularly in PAD effectiveness and self-sufficiency ratios. Fiscal decentralization remained strong, demonstrating Bali's solid fiscal capacity. The pandemic induced budget shifts towards urgent sectors, affecting expenditure efficiency and capital spending patterns. Overall, Bali’s financial management showed resilience and recovery, though efficiency improvements remain necessary. This study offers valuable insights into regional fiscal management during crises and recommendations for enhancing fiscal independence and stability in the future.